Nessuno poteva aprire il libro... Miscellanea di studi e testimonianze per i settant'anni di fr. Silvano Danieli, OSM - Guerrini, Mauro (Biblioteche & bibliotecari / Libraries & librarians, 2019)
The initiative to offer one Festschrift to Silvano M. Danieli for his seventieth birthday pays tribute to a man and a professional whose work has left a deep mark on human relations and on the world of libraries. Silvano, librarian at the Pontifical Theological Faculty "Marianum" and Prior of the Studio Marianum community in Rome since 2014, has indeed played a strategic role in the development of URBE, the association unifying the libraries of Rome's pontifical universities in a single network of services. The qualified list of Italian and European participants to the work is proof of the breadth of appreciation he earned in his thirty years of activity as librarian and curator of the Bibliography of the Servite Order and of the Marian Bibliography. Aelredo of Rievaulx (1109-1167), one of the leading figures of the Anglo-Saxon Cistercian monasticism, expresses the meaning of this gift with the following words: «A man, by virtue of the friendship he has towards another man, becomes a friend of God, according to what the Lord says in the Gospel: I no longer call you servants, but friends»(De spirituali amicitia, II, 14).